Beta-lactamase determinants and molecular typing of carbapenem-resistant classic and hypervirulent Klebsiella pneumoniae clinical isolates from southwest of Iran - Saki, Morteza; Amin, Mansour; Savari, Mohammad; Hashemzadeh, Mohammad; Seyedian, Seyed Saeid (Frontiers in Microbiology, 2022)
This study investigated the molecular epidemiology of carbapenem-resistant classic Klebsiella pneumoniae (CR-cKp) and carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKp) isolates in southwestern Iran. From 2019 to 2021, 136 (88.9%) cKp and 17 (11.1%) hvKp isolates were identified using biochemical tests and polymerase chain reaction (PCR). Antibiotic resistance, beta-lactamases, and clonal relatedness of carbapenem-resistant isolates were investigated using disc diffusion, PCR, and enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR), respectively. The different markers of hvKp isolates were as follows: string test (35.3%, n = 6/17), magA (11.8%, n = 2/17), rmpA (11.8%, n = 2/17), rmpA2 (52.9%, n = 9/17), iucA (52.9%, n = 9/17), and peg344 (35.3%, n = 6/17). Also, 55.1% (n = 75/136) of cKp and 47.1% (n = 8/17) of hvKp isolates were CR-cKp and CR-hvKp, respectively. All CR-hvKp (100.0%, n = 8) isolates were MDR. Colistin, tetracycline, and tigecycline were the most effective antibiotics. The occurrence of beta-lactamase genes in 75 CR-cKp and 8 CR-hvKp isolates was as follows: blaNDM (41.3%, 25.0%), blaIMP (4.0%, 0.0%), blaVIM (8.0%, 0.0%), blaGES (14.7%, 25.0%), blaOXA-48-like (20.0%, 0.0%), blaCTX-M (26.7%, 12.5%), blaSHV (24.0%, 12.5%), blaTEM (10.7%, 0.0%), blaFOX (6.7%, 0.0%), blaDHA (6.7%, 0.0%), blaCMY (5.3%, 0.0%), blaLAT (12.0%, 0.0%), and blaACT (8.0%, 0.0%). ERIC-PCR showed a high diversity among isolates. In this study, the occurrence of MDR CR-hvKp isolates harboring blaNDM and blaGES was detected for the first time in southwestern Iran. To prevent the spread of CR-hvKp and reduce selection pressure, long-term surveillance and more effective treatment strategies should be implemented.